2011
DOI: 10.1016/j.memsci.2011.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Membrane fouling due to dynamic particle size changes in the aerated hybrid PAC–MF system

Abstract: a b s t r a c tTo quantify the effect of dynamic particle size changes and degradation and accumulation of suspended solids (SS) in influents to reactors on membrane fouling frequency in hybrid powder-activated carbon (PAC)-microfiltration (MF) reactors, we operated a PAC-MF system (hollow-fiber module) for more than five months to purify river water before and after pretreatment by a biofilter. The transmembrane pressure, backwashing pressure, resistance to filtration, and SS accumulation and degradation duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…Meanwhile, the microbial cells attached to PAC secrete enzymes into the micropores which leads to extracellular biodegradation of adsorbed organics. The mechanisms mentioned above are probably responsible for higher biodegradation efficiency with PAC (Satyawali and Balakrishnan, 2009a;Khan et al, 2011). Results show long PAC sludge ages suggested more resistance to high OLR and the stability of effluent quality has been enhanced with PAC which are in good agreement with previous literatures (Sher et al, 2000;Munz et al, 2007;Taimur Khan et al, 2013).…”
Section: Influences Of Pac On Mbr Performance With High Loading Ratessupporting
confidence: 90%
“…Meanwhile, the microbial cells attached to PAC secrete enzymes into the micropores which leads to extracellular biodegradation of adsorbed organics. The mechanisms mentioned above are probably responsible for higher biodegradation efficiency with PAC (Satyawali and Balakrishnan, 2009a;Khan et al, 2011). Results show long PAC sludge ages suggested more resistance to high OLR and the stability of effluent quality has been enhanced with PAC which are in good agreement with previous literatures (Sher et al, 2000;Munz et al, 2007;Taimur Khan et al, 2013).…”
Section: Influences Of Pac On Mbr Performance With High Loading Ratessupporting
confidence: 90%
“…In the past decades, microfiltration (MF) has emerged as one of the most reliable, cost-effective and sustainable unit processes for surface water treatment separating macromolecules, bacteria and discrete particles (Lebeau et al, 1998;Khan et al, 2001Khan et al, , 2011Fabris et al, 2007). In this process, biofouling has been identified as the key factor affecting long-term MF membrane separation processes and worsening overall plant performance.…”
Section: Introductionmentioning
confidence: 99%
“…This result indicates that PAC cake layer played a positive role in terms of membrane fouling. Previous researchers [5][6][7][8][9][10][11][12][13][14][15] also reported that addition of PAC resulted in the formation of larger particles and reduced TMP increase.…”
Section: Filtration Resistance With/without Cake Layermentioning
confidence: 99%